2009
DOI: 10.1093/jxb/erp330
|View full text |Cite
|
Sign up to set email alerts
|

Sporophytic control of pollen tube growth and guidance in maize

Abstract: Pollen tube germination, growth, and guidance (progamic phase) culminating in sperm discharge is a multi-stage process including complex interactions between the male gametophyte as well as sporophytic tissues and the female gametophyte (embryo sac), respectively. Inter- and intra-specific crossing barriers in maize and Tripsacum have been studied and a precise description of progamic pollen tube development in maize is reported here. It was found that pollen germination and initial tube growth are rather unsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…Chemoattractants located in the pistil are thought to guide pollen tubes toward the ovules. [43][44][45] Recent reports showed that female gametophytes respond to stigma pollination or pollen tube growth through the female transmitting track, supporting the existence of long distance signaling pathways. The expression of the AMC gene, named after the abstinence by mutual consent mutant, encodes a peroxin required for protein import into peroxisomes and essential for pollen tube discharge, is induced in the embryo sac by pollen deposition on the stigma.…”
Section: Ros and Embryo Sac Fertilizationmentioning
confidence: 93%
“…Chemoattractants located in the pistil are thought to guide pollen tubes toward the ovules. [43][44][45] Recent reports showed that female gametophytes respond to stigma pollination or pollen tube growth through the female transmitting track, supporting the existence of long distance signaling pathways. The expression of the AMC gene, named after the abstinence by mutual consent mutant, encodes a peroxin required for protein import into peroxisomes and essential for pollen tube discharge, is induced in the embryo sac by pollen deposition on the stigma.…”
Section: Ros and Embryo Sac Fertilizationmentioning
confidence: 93%
“…Unlike animals, which have sperm cells (SCs) that travel through self-propelled flagellum, flowering plants use pollen tubes to deliver SCs to ovules (10)(11)(12)(13). In Arabidopsis, pollen tube growth is guided by chemical cues in carpel tissues and attracted by small peptides secreted by synergid cells in the vicinity of ovules (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Subsequently, ovaries were immersed in 5% NaOH overnight and then, rinsed with distilled water and 50 mM KPO 4 . They were stained with 0.01% decolorized aniline blue in 50 mM KPO 4 for 20 min (Lausser et al 2010) and observed under UV using a Zeiss Axiophot epifluorescence microscope.…”
Section: Pollen Tube Observationsmentioning
confidence: 99%
“…Pollen tube growth in maize has been well studied (Adams and Mackay 1953;Kiesselbach 1980;Heslop-Harrison et al 1985;Styles 1987;Kliwer and Dresselhaus 2010;Lausser et al 2010). Germination of pollen grains and the growth of pollen tubes of Balsas teosinte are generally similar to those of maize.…”
Section: Pollen Tube Growthmentioning
confidence: 99%